Tadrīs al-Lughah al-‘Arābīyah fī al-Madāris al-Sharqīyah al-Taqlīdīyah al-Dīnīyah fī Sharq Turkiyā: Madāris Tillo and Jazīrat Ibn ‘Umar Numūdhajan - Mohammed Emin Nas (Universitas Negeri Jakarta, 2018)
The research aims to identify the traditional religious schools in Eastern Turkey in general with a historical and descriptive perspective. It will also focus on these educational institutions in terms of their programs and curricula in teaching Arabic to non-native speakers about some important historical developments relating to and affecting them. We will also analyze publications and books circulating in the hands of teachers and students in these institutions (in Tillo and Jazeera) and address them descriptively and concisely. We will examine these institutions in terms of particular characteristics such as formality, descriptive, financial sources, and development in the current time. Finally, we will identify the extent of the attractiveness of graduates amongst citizens and their status in society, and the employment and permanence of graduates from these institutions. The method of research is through descriptive, analytical, and comparative methods. The research concludes that the basis of teaching in this school is primarily voluntary free teaching. The method of teaching is to take the lessons either individually or in a group and to memorize the text and then supplement than with commentaries deeply and logically before and after the class. The system by which the books are taught are systematically and to complete them in entirety.